Amidst the priesthood and activism: the everyday life of a school in the countryside of Valença - RJ - Érica Alves da Silva Fartes; Renan Santiago de Sousa (Universidade Federal do Norte do Tocantins, 2020)
The objective of this research was to analyze the daily life of a teacher in a public school located in the city of Valença - RJ. According to Alves (2003), each day of the school is different, therefore, it is necessary that different types of studies show how knowledge is constructed and reconstructed in the school environment, as well as highlight what are the expectations of the teacher in relation to teaching and report the their working conditions. This is a qualitative research (Gerhartdt & Silveira, 2009), which were produced through on-site observations of the school's daily life and based on a semi-structured interview conducted with the teacher. Once produced, the data were analyzed via categorization (Moraes, 1999). The results point to the precariousness of the school, the difficulties that the teacher goes through in the exercise of teaching and a mixture of hope and pessimism in relation to the changes in the actions of the authorities in relation to rural education.